Удосконалення диспетчерського керівництва дільниці на основі прогнозного моделювання перевізного процесу - Долгополов, Петро Віталійович; Головко, Тетяна Владиславна; Галишинець, Тарас Володимирович; Іванова, Юлія Андріївна (НТУ "ХПІ", 2015)
Розроблено заходи з розширення функціонального складу диспетчерських систем управління. Розроблена модель побудови прогнозного графіку руху поїздів з урахуванням оперативних факторів перевізного процесу: діючі попередження, маса состава та потужність локомотивів, змінні станційні інтервали, наявність та довжина пасажирських платформ. Результати дослідження дозволяють формувати найбільш ефективний прогнозний графік руху поїздів, застосування якого підвищує дільничну швидкість та скорочує витрати на зупинки поїздів на дільниці.

The plan of extention of the control systems’ functional structure has been developed. Here is the developed model of creating the forecast chart of trains movement including operational factors of transportation process: current warnings, mass of train and capacity of locomotives, variable station intervals, availability and length of passengers platforms. Results of the research allow calculation and releasing of the most effective forecast schedule of trains movement to train dispatcher. The use of schedule increases speed on the road section and reduces expenses on train stops. The proposed technology allows you to determine the optimal schedule of trains at each of their inconsistent approach to the railway district. This significantly reduces non-productive downtime of trains in times of concentration of train flows, in cases of unscheduled trains and at closing spans for repairs.
Improvement of the dispatch control at the railway district on predictive modeling of the transportation process
Keywords: диспетчерська централізація; поїзний диспетчер; станційний інтервал; прогнозний графік руху поїздів; centralized traffic control; train dispatcher; station intervals; schedule of trains movement